Effects of diglossia on classical Arabic: language developments in bilingual learners - Ahmad Oueini,; Awada, Ghada; Kaissi, Fatima S. (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this study is to investigate the effects of Arabic diglossia on the development of classical Arabic language acquisition amongst bilingual learners in a private school in Lebanon. The study compares the Arabic language (L1) performance to that of English as a Foreign Language (EFL) in accordance with Bialystok’s model. One hundred-forty participants; (n=140), ranged from five to eleven years of age, with a mean of eight years were sampled. A two-stage random sampling technique was applied, while ensuring that students with contrastive academic achievement were included within the study. The participants sampled for this correlational research were learners enrolled at a private middle school. Participants were given two standardized measures so as to establish the trend of development in oral skills for both classical and colloquial Arabic, determine the grade level at which convergence occurs between the two forms of acquisition and finally compare the degree of classical Arabic (L1) acquisition with respect to their EFL acquisition. The findings indicated interrelatedness between Arabic diglossia and the late oral development of classical Arabic, whereas participants showed a higher degree of comfort with English than with their mother language. Recommendations for future directions and research are also given.